Tone Concavity around Expected Earnings - D'Augusta, Carlo; DeAngelis, Matthew D. (The Accounting Review, 2020)
ABSTRACT We examine whether the relationship between managerial tone and earnings performance depends on the performance of the firm relative to earnings expectations. Using both annual changes in earnings and the difference between realized earnings and analyst consensus forecasts, we find evidence of “tone concavity” around earnings expectations. Specifically, the covariance between managerial tone and earnings performance is positive when earnings are below expectations, but negative when earnings meet or exceed expectations. We interpret our results to suggest that managers downplay positive changes in earnings to attenuate future growth expectations. We also find that tone concavity is significantly attenuated by managers' career concerns and accounting conservatism, but unrelated to litigation risk. Our results indicate that the effect of earnings performance on disclosure tone is complex and reflects managers' incentives to manage expectations.